Dinamika hidrokimia air tanah pada Akuifer Pasiran Pulau Yeben Raja Ampat, Papua Barat - Septian Vienastra; Erik Febriarta (Jurnal Pendidikan Geografi, 2021)
The quality of coastal ground water on small islands has characteristics that are influenced by environmental and area factors. Yeben Island is a small island with an area of 0.57 km2 with priority coastal and marine tourism areas in the islands of Raja Ampat. This study aims to (1) analyze levels of ground water quality parameters and (2) analyze water samples against water quality standards. Groundwater samples taken as many as 4 samples from the study location. The location of water samples is in the morphology of the coastal plain. The analysis of each physical and chemical parameter of each groundwater sample is carried out by comparing the value of drinking water quality standards. The results are presented in a comparison table of quality standards and a graph of scaled values.Based on the results, the laboratory shows that it exceeds the quality standard of physical elements and chemical elements including fluoride, hardness, sulfate and organic substances. In general, the quality of water is poor. Poor ground water quality occurs due to the influence of sea water intrusion. Kualitas air tanah pesisir di pulau kecil memiliki karakteristik yang dipengaruhi oleh faktor lingkungan dan luasan. Pulau Yeben merupakan pulau kecil dengan luas 1,3 km2 dengan prioritas kawasan pariwisata pesisir dan bahari di kepulauan Raja Ampat. Penelitian ini bertujuan untuk (1) menganalisis kadar parameter kualitas air tanah dan (2) menganalisis sampel air terhadap baku mutu air. Sampel air tanah yang diambil sejumlah 4 sampel dari lokasi kajian. Lokasi sampel air berada pada morfologi dataran pantai. Analisis setiap parameter fisik dan kimia masing-masing sampel air tanah dilakukan dengan perbandingan nilai standar baku mutu air minum Hasil penelitian disajikan dalam tabel perbandingan baku mutu dan grafik nilai berskala. Berdasarkan hasil laboratorium menunjukkan melebihi baku mutu unsur fisik dan unsur kimia antara lain fluorida, kesadahan, sulfat dan zat organik. Secara umum kualitas air termasuk buruk. Kualitas air tanah yang buruk terjadi dikarenakan oleh pengaruh intrusi air laut.